Cajal bodies and their role in plant stress and disease responses. Issue 6 (3rd June 2017) - Love, Andrew J.; Yu, Chulang; Petukhova, Natalia V.; Kalinina, Natalia O.; Chen, Jianping; Taliansky, Michael E.
ABSTRACT: Cajal bodies (CBs) are distinct sub-nuclear structures that are present in eukaryotic living cells and are often associated with the nucleolus. CBs play important roles in RNA metabolism and formation of RNPs involved in transcription, splicing, ribosome biogenesis, and telomere maintenance. Besides these primary roles, CBs appear to be involved in additional functions that may not be directly related to RNA metabolism and RNP biogenesis. In this review, we assess possible roles of plant CBs in RNA regulatory pathways such as nonsense-mediated mRNA decay and RNA silencing. We also summarize recent progress and discuss new non-canonical functions of plant CBs in responses to stress and disease. It is hypothesized that CBs can regulate these responses via their interaction with poly(ADP ribose)polymerase (PARP), which is known to play an important role in various physiological processes including responses to biotic and abiotic stresses. It is suggested that CBs and their components modify PARP activities and functions.